ANALISA PENINGKATAN KUALITAS PRODUK DENGAN NEW QUALITY CONTROL TOOLS - Agung Hananto; Eko Arianto (Politeknik Meta Industri, 2022)
Politeknik Industri ATMI is a vocational education institution that beside carrying out the educational process, ATMI has a production division that aims to carry out order-based production in order to increase the income for education funds. The products produced are custom products ordered by customers which have different process variations. The object of the research is the production processed in the lathe and milling practical section. The percentage of defective products in this division in the period January 2022 - October 2022 reach 8% higher than the specified procentage, which should not exceed 5% defects form the products produced. Problems related to product quality lead to increase production operational costs as a result of repeat production process or rework. This activity can cause loss of customers due to disappointment over poor product results. This research activity was carried out to find problems in product defects, find the root of the problem and propose improvements. All possibilities that affecting Product defects are evaluated using an affinity diagram which produces 5 parts that can be the cause of defects, namely: Humans, Materials, Processes, Equipment and Systems. These results explore further the relationship between one another using an interrelationship diagram. Tree diagrams are used to obtain factors that can be used as suggestions for improvements to the corrections of problems found. The improvement to the corrections suggestions are: Recruiting competent employees; Employee training / training; Implementation of inherent quality control; Application of SOP in production; Making clear job descriptions; Implementation of 5R and K3; Routine machine maintenance. Using a complete matrix diagram with the analysis carried out, it is obtained a sequence of possible improvements to be made in order to improve quality, namely the first is the application of inherent quality control; the second order is the application of SOP in production; third is the implementation of 5R and K3; fourth is recruiting competent employees, employee training / training or routine machine maintenance; fifth is making a clear job description.